Nutcracker Syndrome Complicated by Left Renal Vein Thrombosis - Faouzi Mallat; Wissem Hmida; Mehdi Jaidane; Nadia Mama; Faouzi Mosbah (Case Reports in Urology)
Isolated renal vein thrombosis is a rare entity. We present a patient whose complaint of flank pain led to the diagnosis of a renal vein thrombosis. In this case, abdominal computed tomography angiography was helpful in diagnosing the nutcracker syndrome complicated by the renal vein thrombosis. Anticoagulation was started and three weeks later, CTA showed complete disappearance of the renal vein thrombosis. To treat the Nutcracker syndrome, we proposed left renal vein transposition that the patient consented to.